Hubungan Kompetensi Kepribadian Guru dengan Prestasi Belajar Siswa di SMP Muhammadiyah 2 Kalasan - Susetyowati, Tisa; Susena, Susena (Universitas Ahmad Dahlan, 2013)
Teachersâ personality competence is the personal ability that reflects the personality of steady, stable, adult, wise and prestigious, to be noble and a model for students. The mastery of teachersâ personality competence is significance, both for school and especially for the students. By the teachersâ personality competence, the teachers can not be separated from the hard working of students in learning that can be demonstrated through an attitude while teaching-learning activities (KBM), student activity, student achievement, the value in Civics subject which is packaged in the form of number such as the value of student report cards of Civics subject. The purpose of this research is to understand the relationship of teachersâ personality competence with studentsâ learning achievement. The population of this research is all students of the 7th graders of SMP Muhammadiyah 2 Kalasan in the academic year of 2012/ 2013 totaling of 140 students. The samples of this research are 100 students that divided into four classes. The researcher collects the data by a questionnaire which is used to measure teachersâ personality competence of Civics teacher and it uses documentation in the form of report cards of grades in Civics subjects. The data analysis method which used is correlation analysis product moment then examines by t-test so that it can be seen that the relationship of positive and significant of two variables. Based on the results of the data analysis, the researcher concludes that the correlation between teachers personality competence with studentsâ learning achievement is 0.518. It means that there is a positive and significant relationship between teachers personality competence with studentsâ learning achievement in Civics of the 7th graders of SMP Muhammadiyah 2 Kalasan in the academic year of 2012/ 2013.